Implementation of Problem‐Based Learning by Faculty Members at 12 U.S. Medical and Dental Schools. Issue 11 (1st November 2016) - Abdelkarim, Ahmad; Schween, Dorothy; Ford, Timothy
Abstract : The aim of this study was to assess the perspectives of medical and dental faculty members regarding implementation of problem‐based learning (PBL). A survey instrument was designed with demographic questions and two open‐ended questions to investigate faculty members' perceptions of the most suitable subjects or courses in which to use PBL and examples of how they incorporated PBL into their instruction. The survey was sent to 12 U.S. medical and dental schools known to use PBL, and 73 medical faculty members and 88 dental faculty members completed the survey (n=161), for an overall response rate of 28% of those who were sent the survey at each school (not each's total faculty). In the results, 41% of the medical faculty respondents and 22% of the dental faculty respondents stated that PBL is applicable for all subjects. Members of both groups perceived that PBL is primarily applicable in clinical education, including clinical courses or the clinical applications of courses. The respondents' perceptions about PBL implementation varied significantly, and both groups reported a wide range of approaches in which they implement PBL in their instruction, some of which were not consistent with the purpose of PBL.